Preconditioning donors with corticosteroids improves early lung graft immunity - Schwartz-Cornil, Isabelle; Pascale, Florentina; Jouneau, Luc; Huriet, Maxime; Estephan, Jérôme; Bourge, Mickael; Richard, Christophe; Gelin, Valérie; Bevilacqua, Claudia; Rivière, Julie; Vu Manh, Thien-Phong; Djebbour, Maxime; et al. (Frontiers in Immunology, 2025)
BackgroundPreclinical studies have recently revealed the critical role of innate immunity in determining lung transplantation outcomes. Although the International Society for Heart and Lung Transplantation recommends high-dose corticosteroid administration to donors, this practice is inconsistently applied worldwide. Investigating its impact on the donor lung’s innate immune response – an unexplored area - could provide valuable evidence to support adoption of donor preconditioning with corticosteroids, beyond their traditional administration to recipients.MethodWe used a cross-circulatory pig platform that consists of a donor lung placed extracorporeally and connected to the circulation of a recipient pig whose leukocytes are fluorescently labeled.ResultsDonor preconditioning - compared to recipient’s treatment alone - reduced the presence of CD3pos T-cells in the graft from both the donor and recipient, and enhanced the anti-inflammatory profile of alveolar macrophages, at least during the first 10 hours of donor-recipient interaction. The alveolar macrophages isolated from corticosteroid-preconditioned pig lungs exhibited decreased gene expression of T-cell-attracting chemokines during the 10-hour reperfusion period, correlating with the reduced T-cell infiltration. Similarly, human lung macrophages showed lower expression of these T-cell-attracting chemokines and higher anti-inflammatory profiles with corticosteroid treatment.ConclusionOur results show that the early immune status of lung grafts is improved by treating donors with corticosteroids through macrophage-targeted mechanisms. This finding provides an immunological rationale for expanding the implementation of donor preconditioning with corticosteroids.